Biobased Polylactide Nanoparticles as Novel Gene Delivery Nanoplatforms: Can They Be Used for DNA Transport? - Farnaz Sadat Fattahi (Nanochemistry Research)
Gene therapy is a rapidly progressing field with vast prospective for fundamentally treating human diseases such as cancer, damaged tissues, and genetic syndromes. Between various approaches of gene delivery, there is a growing interest in oral administration of DNA as one of the safest and most straightforward methods. Nanoparticles are some of the important examples of nano-materials for molecule delivery (drugs, growth factors and DNA) used in biomedical applications. Several researchers have revealed the process of nanotechnology, specifically polymeric nanoparticles, as DNA delivery structures for transdermal routines. Polylactic acid (PLA) and its famous co-polymer polylactic-co-glycolic (PLGA) are biocompatible synthetic polymers widely used to produce nanoparticles. Biobased, biosourced, biodegradable biocompatible, and bioabsorbable polylactide nanoparticles are one of the most promising materials in gene therapy serving as DNA delivery vehicles. Polylactide nanoparticles are easily processable and undergo degradation into natural metabolites while matching its degradation rate with the healing time of damaged human tissues. This mini review presents the new developments in the applications of polylactide nanoparticles as DNA delivery systems. In addition, the release of DNA from these nanoplatforms will be reported briefly.